Biochemical composition and antioxidant capacity of extracts from Podophyllum hexandrum rhizome - Li Mengfei; Zhou Lanlan; Yang Delong; Li Tiantian; Li Wei (BMC, 2012)
Abstract Background Podophyllum hexandrum Royle (P. hexandrum) is a perennial herb and widely used in clinic. The present study was designed to separate and identify the biochemical composition and antioxidant capacity of extracts from P. hexandrum rhizome. Methods The ethyl acetate and ethanol extracts from P. hexandrum rhizome were analyzed by GC-MS (gas chromatography-mass spectrometry), and the antioxidant capacity of the extracts and the components was tested by using the DPPH (2, 2-diphenylpicrylhydrazyl) and FRAP (Ferric reducing/antioxidant power) assays. Results The rhizome extracts had greater antioxidant capacity than the petiole extracts in DPPH and FRAP assays. About 16 kinds of main reactive oxygen components were identified in the extracts. Components of PADE (Phthalic acid, diisobutyl ester), BADE (1,2-Benzenedicarboxylic acid, diisooctyl ester), Polyneuridine, PODD (Podophyllotoxin, deoxy), β-Sitosterol and POD (Podophyllotoxin) showed the antioxidant capacity in some degree. PODD, POD, and Polyneuridine showed stronger antioxidant capacity with the IC50 and FRAP values of 9.61 ± 0.81 and 2923.98 ± 21.89 μM, 9.98 ± 0.24 and 2847.27 ± 14.82 μM, and 13.37 ± 0.35 and 2404.32 ± 36.88 μM, respectively, than the positive control ASA (Ascorbic acid) with the values of 60.78 ± 1.22 and 1267.5 ± 30.24 μM (P < 0.01). Conclusions PODD, POD, and Polyneuridine are very critical for the antioxidant capacity in the extract of P. hexandrum rhizome. These results provide useful biochemical basis and information for the potential use of this plant.